Factors predicting desistance from reoffending: a validation study of the SAPROF in sexual offenders - Yoon, Dahlnym (International journal of offender therapy and comparative criminology, 2018)
The present study aims at validating the German version of the Structured Assessment of PROtective Factors (SAPROF) for violence risk in a representative sample of incarcerated adult male sexual offenders. Sexual offenders (n = 450) were rated retrospectively with the SAPROF using the database of the Federal Evaluation Centre for Violent and Sexual Offenders (FECVSO) in the Austrian Prison System. Interrater reliability and predictive validity of the SAPROF scores concerning desistance from recidivism were calculated. Concurrent and incremental validity were tested using the combination of the SAPROF and the Sexual Violence Risk-20 (SVR-20). Interrater reliability was moderate to excellent, and predictive accuracy for various types of recidivism was rather small to moderate. There was a clear negative relationship between the SAPROF and the SVR-20 risk factors. Whereas the SAPROF revealed itself as a significant predictor for various recidivism categories, it did not add any predictive value beyond the SVR-20. Although the SAPROF itself can predict desistance from recidivism, it seems to contribute to the risk assessment in convicted sexual offenders only to a limited extent, once customary risk assessment tools have been applied. Implications for clinical use and further studies are discussed.